Parties as Governments in Eurasia, 1913-1991 Nationalism, Socialism, and Development - Sablin, Ivan; Bandeira, Egas Moniz (Routledge Studies in the Modern History of Asia, 2022)
This book examines the political parties which emerged on the territories of the former Ottoman, Qing, Russian, and Habsburg empires and not only took over government power but merged with government itself. It discusses how these parties, disillusioned with previous constitutional and parliamentary reforms, justified their takeovers with programs of controlled or supervised economic and social development, including acting as the mediators between the various social and ethnic groups in the respective territories. It pays special attention to nation-building through the party, to institutions (both constitutional and de facto), and to the global and comparative aspects of one-party regimes. It explores the origins of one-party regimes in China, Czechoslovakia, Korea, the Soviet Union, Turkey, Yugoslavia, and beyond, the roles of socialism and nationalism in the parties' approaches to development and state-building, as well the pedagogical aspirations of the ruling elites. Hence, by revisiting the dynamics of the transition from the earlier imperial formations via constitutionalism to one-party governments, and by assessing the internal and external dynamics of one-party regimes after their establishment, the book more precisely locates this type of regime within the contemporary world's political landscape. Moreover, it emphasises that one-party regimes thrived on both sides of the Cold War and in some of the non-aligned states, and that although some state socialist one-party regimes collapsed in 1989-1991, in other places historically dominant parties and new parties have continued to monopolize political power. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.